1995
DOI: 10.1111/j.1469-8137.1995.tb03044.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SO2 on the concentrations of carbohydrates and secondary compounds in Scots pine (Pinus sylvestris L.) and Norway spruce (Picea abies (L.) Karst.) seedlings

Abstract: SUMMARYScots pine {Pinus sylvestris L.) and Norway spruce {Picea abies (L.) Karst.) seedlings of open-pollinated progenies and clonal cuttings were exposed to various concentrations of SOj (50-155 nl T') in several growth chamber experiments. No visible foliar injury was observed in any SO.^ exposure. The total sulphur concentrations of the exposed needles were significantly greater than in the control needles. Exposure to SO.^ (100 and 155 nll"^) reduced concentrations of glucose and fructose and increased co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…This is probably because wax esters are only abietic acid might be largely infiuenced by phenotype hydrolysed at extreme acidities (pH < 3). Such (Kainulainen, Holopainen & Oksanen, 1995), since conditions are probably restricted to localized areas the subarctic Scots pines exposed to H2SO4, CuSO^ on the needle surface, e.g. as a result of repeated and NiSO4 at pH 3 (4-4 g S m"^ 0-04 g Cu m^^ wetting-evaporation cycles (Milne, g Ni m"^^) for two and a half growing seasons did Henderson, 1990;Percy et al, 1994).…”
Section: Wax Chemical Compositionmentioning
confidence: 99%
“…This is probably because wax esters are only abietic acid might be largely infiuenced by phenotype hydrolysed at extreme acidities (pH < 3). Such (Kainulainen, Holopainen & Oksanen, 1995), since conditions are probably restricted to localized areas the subarctic Scots pines exposed to H2SO4, CuSO^ on the needle surface, e.g. as a result of repeated and NiSO4 at pH 3 (4-4 g S m"^ 0-04 g Cu m^^ wetting-evaporation cycles (Milne, g Ni m"^^) for two and a half growing seasons did Henderson, 1990;Percy et al, 1994).…”
Section: Wax Chemical Compositionmentioning
confidence: 99%
“…Phenolic compounds including lignin are one of the groups of carbon-based protective chemical compounds, which contribute to resistance against herbivores (Honkanen et al, 1999). Changes in deposition of soluble phenolics and lignin are documented as a response to various stresses, including herbivores (Tuomi et al, 1989) and atmospheric pollution (Kainulainen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Katoh et al (1989b) showed decreased concentrations of soluble phenols in Cryptomeria japonica exposed to ozone, which was correlated with lower levels of glucose and shikimic acid. Kainulainen et al (1995) observed a decrease of glucose, frutose and soluble phenols in needles of Pinus sylvestris and Picea abies when exposed to SO 2 . The lower photosynthetic capacity of the young plants of T. pulchra exposed to the air of VM, found by Pradella (1997) and Moraes (unpublished data), may indicate a possible correlation between alterations on photosynthesis, carbohydrate metabolism and decreased concentrations of total soluble phenols and tannins.…”
Section: Resultsmentioning
confidence: 86%